Twelve tips for integrating Virtual Reality Simulation into Health Professions Curricula [version 1; peer review: 2 approved] - Yvonne Finn; Siobhan Smyth (MedEdPublish, 2024)
Virtual reality simulation (VRS) has the potential to disrupt and transform current understandings and practices in simulation-based education in health professions curricula. Recent technological developments, including AI applications, give the learner high levels of immersion into a virtual environment that even more closely mimic the real world than heretofore. At the same time, there are significant obstacles facing educators who strive to integrate VRS into their simulation curricula. We have written a VRS handbook for nurse educators, developed VR scenarios and delivered VRS workshops to undergraduate nursing students. Our twelve tips are aimed at undergraduate curriculum developers and simulation leaders, guiding them on how to support educators in integrating VRS into their curricula. The tips describe key considerations to be addressed in the development and integration of VRS into curricula. The tips are timely, as health professions education is on the cusp of entering technology-enhanced simulation, of which VRS will be a key player.